Reaching Out to Africa's Orphans : A Framework for Public Action - Subbarao, Kalanidhi; Coury, Diane (Washington, DC: World Bank, 2013)
The study begins by stressing three points. First, the number of orphans is growing at an alarming rate, and therefore the vulnerabilities associated with orphanhood require immediate attention. Second, because resources are limited and not all orphans are in need of assistance, there is an urgent need to target assistance to the neediest children in a nonstigmatizing fashion, within the framework of the present limited knowledge of what works and what does not. Third, although there is still no blueprint on the best way to scale up interventions, the World Bank's multicountry AIDS programs (MAPs) do offer an opportunity not only to pilot assistance efforts but also to extend assistance to as many of the needy as possible, albeit seeking interagency coordination of efforts both to avoid duplication of efforts and to learn from the experience of everyone involved in this effort. An important rationale for such an intervention is to ensure that orphans' human development (access to health care and education) is not in any way jeopardized. Clearly, the challenge faced by all stakeholders and donors in channeling assistance to the affected children is enormous.